Spiritualisme dan Politik (Filosofi dalam Politik di Indonesia) - Utomo, Wahyu Wiji; Aswin, Muhammad (Jurnal Review Politik, 2020)
Many people consider politics as a tool to gain power, it is not wrong but on the other hand politics has a noble purpose. The purpose of this study focuses on the political problems in Indonesia which experience spiritual emptiness and the influence of the spiritualism movement on politics. The method used is a qualitative method with descriptive analysis research to see various aspects of current political problems. As a result of the spiritual emptiness it was found that the politics that developed did not have a direction and purpose, so politics was oriented only to power and not to the people. With this, at least politics in Indonesia must return to the philosophical spirit, which is the welfare of the people. The solution offered is the idea of improving political spiritualism, with religion as the basis for improving the current political situation.